ANALISIS TINGKAT BEBAN KERJA PEGAWAI PADA LEMBAGA X - Haura Yanjani; Christian Wiradendi Wolor; Eka Dewi Utari (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This research aims to analyze the level of employee workload at Institution X, by highlighting the form of perceived burden, factors that influence workload, and its impact on performance. This research uses a descriptive qualitative approach with a case study method to obtain an in-depth picture through observation, interviews, documentation, and literature study. The results showed that employee workload is fluctuating and influenced by imbalance in task distribution, limited facilities and infrastructure, time pressure, and changes in work procedures. This condition has an impact on work effectiveness, employee welfare, and work patterns that tend to change from collaborative to individual. Although management efforts have been made, such as optimizing task distribution and improving coordination, there are still obstacles in its implementation, especially in cross-team coordination. This research recommends evaluating a more equitable distribution of tasks, time management training, and strengthening work policies that support the balance between workload and individual capacity.